2009
DOI: 10.1111/j.1439-0531.2009.01528.x
|View full text |Cite
|
Sign up to set email alerts
|

Follicular, Oocyte and Embryo Features Related to Metabolic Status in Primiparous Lactating does Fed with High-Fibre Rearing Diets

Abstract: Fertility of primiparous lactating does in the early postpartum (pp) period is very low mainly due to pronounced deficient energy intake, influencing oocyte and embryo developmental competence. The hypothesis used in this work was that high-lignin fibre diet supplied during the rearing period could increase feed intake and, consequently, improve the reproductive physiology and metabolic status of primiparous does in the early pp period. Diets with high-lignin [HL: 15.8% dry matter (DM)] or standard-lignin cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
1
5
0
1
Order By: Relevance
“…This is probably because in early stages of gestation corpora lutea produce scant but still enough amount of progesterone to sustain early embryo events which also could explain the similar embryo development observed in the current study. On the other hand, embryo rate was similar to that usually obtained on 3.5 days after AI as previously described (Arias-Álvarez et al, 2010). In this regard, in cows, Fouladi-Nashta et al (2009) confirmed that despite altering proportions of major FA in plasma and milk, dietary PUFA supplementation had little effect on FA composition of granulosa cells, and consequently, there was no effect of diet on follicle numbers and post-fertilization development of oocytes in vitro.…”
Section: Discussionsupporting
confidence: 87%
“…This is probably because in early stages of gestation corpora lutea produce scant but still enough amount of progesterone to sustain early embryo events which also could explain the similar embryo development observed in the current study. On the other hand, embryo rate was similar to that usually obtained on 3.5 days after AI as previously described (Arias-Álvarez et al, 2010). In this regard, in cows, Fouladi-Nashta et al (2009) confirmed that despite altering proportions of major FA in plasma and milk, dietary PUFA supplementation had little effect on FA composition of granulosa cells, and consequently, there was no effect of diet on follicle numbers and post-fertilization development of oocytes in vitro.…”
Section: Discussionsupporting
confidence: 87%
“…) compared to does synchronized with eCG (Arias‐Álvarez et al. ,b). Therefore, different treatments should be used along the reproductive life of the does taking into account their reproductive rhythm and age.…”
Section: Reproductive Strategiesmentioning
confidence: 99%
“…; Arias‐Álvarez et al. ; Rebollar et al. ), and consequently, energy ingestion and metabolic status in the early lactating period when a more energetic feed is furnished (Xiccato et al.…”
Section: Nutritional Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Microscopía confocal, tinción con FITC-PNA Indica correcta maduración (Arias-Álvarez et al, 2010;Lee et al, 2006a) …”
Section: Gránulos Corticalesunclassified